Business Analysis Top 100 Companies Of The Adriatic Region - Sekulić, Dejan; Mandarić, Marija (Hotel and Tourism Management, 2013)
All market participants are affected by economic crisis that we have been witnessing the last few years. Consumers are less certain about their wages and employment, and they are forced to change their shopping habits toward buying cheaper products or giving up purchasing certain goods. On the other hand, under such conditions some companies have a fall in sales and consequently generate less income. Others are faced with the loss of markets and customers, while some of them have the ability and strength to successfully adapt to the new circumstances by adjusting their marketing mix. The aim of this paper is to explore the similarities and differences in the performance of the Top 100 companies in the Adriatic Region, and answer the question whether these companies are affected by the economic crisis or immune to it due to a dominant market position and strong brands.